Socio-environmental analysis in Lagoa da Canoa - AL related to the correct disposal of batteries (Research, Society and Development, 2024)
The objective of this work was to investigate the level of knowledge and environmental practice of the inhabitants of the city of Lagoa da Canoa - AL, in relation to the disposal of batteries in the daily life of the community. Initially, and to understand the knowledge of the inhabitants, a quantitative research was carried out in the city's neighborhoods, through the application of a questionnaire, where it was verified what information people have about the proper disposal of batteries, as they contain metals heavy substances with high dissemination power and a surprising ability to accumulate in the human body and in all living organisms, as they are incapable of metabolizing or eliminating them. The data collected makes it clear that there is no adequate selective collection in the municipality for this electronic waste, a factor that contributes to the accumulation of these materials in the environment, requiring awareness work and active actions by those responsible for the adequate collection and disposal of these materials.